ANALYZING THE ECONOMIC ENVIRONMENT USING MACHINE LEARNING - Bataa, Dulguuntuya; Darkhijav, Bayanjargal; Batsukh, Davaasuren (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
Studying and evaluating a country’s trade and business environment ensures economic stability and enhances organizational competitiveness. Business environment assessments serve as a foundation for identifying entrepreneurs’ challenges and determining future development directions. This research aimed to apply machine learning techniques to classify the economic environment data that received the lowest evaluation in the 2020 joint study conducted by the Mongolian National Chamber of Commerce and Industry and the Business School. The study employed machine learning methods, including K-Means clustering, Principal Component Analysis (PCA), and Decision Tree algorithms.